Putting the Protest Back into Protestant - Helmer, Christine (The ecumenical review, 2017)
When Martin Luther nailed his 95 Theses to the door of the Wittenberg Castle Church on 31 October 1517, he did so in protest at abuses in Catholic theology and practice. Contemporary times, too, call for protest. The first protest concerns the revitalization of education and an increased commitment to intellectual excellence. The second protest concerns a recovery of Luther as a figure of protest. While scholars have tamed Luther's dangerous doctrines, the popular imagination still perceives him as an urban legend who spoke truth to power. An expansive notion of scholarship on Luther is required in order to approach a Luther who continues to inspire people around the world. The third protest is a critical protest of Luther's religious intolerance, specifically his anti-Judaism. Christian theologians must acknowledge Luther's anti-Judaism as central to his theology and radically revise this legacy to promote justice in inter-religious relations.